Preparation of Zwitterionic Sulfobetaines and Study of Their Thermal Properties and Nanostructured Self-Assembling Features - Yenglik Amrenova; Arshyn Zhengis; Arailym Yergesheva; Munziya Abutalip; Nurxat Nuraje (Nanomaterials)
Zwitterionic polymers have garnered significant attention for their distinctive properties, such as biocompatibility, antifouling capabilities, and resistance to protein adsorption, making them promising candidates for a wide range of applications, including drug delivery, oil production inhibitors, and water purification membranes. This study reports the synthesis and characterization of zwitterionic monomers and polymers through the modification of linear, vinyl, and aromatic heterocyclic functional groups via reaction with 1,3-propanesultone. Four zwitterionic polymers with varying molecular structures—ranging from linear to five and six membered ring systems—were synthesized: poly(sulfobetaine methacrylamide) (pSBMAm), poly(sulfobetaine-1-vinylimidazole) (pSB1VI), poly(sulfobetaine-2-vinylpyridine) (pSB2VP), and poly(sulfobetaine-4-vinylpyridine) (pSB4VP). Their molecular weights, thermal behavior, and self-assembly properties were analyzed using gel permeation chromatography (GPC), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), transmission electron microscopy (TEM), and zeta potential measurements. The glass transition temperatures (Tg) ranged from 276.52 °C for pSBMAm to 313.69 °C for pSB4VP, while decomposition temperatures exhibited a similar trend, with pSBMAm degrading at 301.03 °C and pSB4VP at 387.14 °C. The polymers’ self-assembly behavior was strongly dependent on pH and their surface charge, particularly under varying pH conditions: spherical micelles were observed at neutral pH, while fractal aggregates formed at basic pH. These results demonstrate that precise modifications of the chemical structure, specifically in the linear, imidazole, and pyridine moieties, enable fine control over the thermal properties and self-assembly behavior of polyzwitterions. Such insights are essential for tailoring polymer properties for targeted applications in filtration membranes, drug delivery systems, and solid polymer electrolytes, where thermal stability and self-assembly play crucial roles.